Strategi Badan Pengembangan Sumber Daya Manusia Provinsi Jawa Timur dalam Upaya Mencegah Kekerasan Berbasis Gender - Nur Amalia, Selvy; Rohman, Abid (IAI Nasional Laa Roiba Bogor, 2025)
This study aims to examine the strategy of the Human Resources Development Agency (BPSDM) of East Java Province in implementing Sustainable Development Goals 5.2, especially through the implementation of the ASN Learning Series 39 Program themed